På vej til at blive mor og far - køn, klasse, etnicitet og race i jordemoderkonsultationer - Larsen, Bolette Frydendahl (Kvinder, Køn & Forskning, 2010)
On the way to parenthood - (re)productions of gender, ethnicity, race and class in midwife consultations.The premise of this article is that subject positions, which parents-to-be hold during pregnancy, influence their future parenthood. The article examines how such subject positions are produced in midwife consultations. It shows how the man in a heterosexual couple is positioned as peripheral while the woman is assigned the responsibility for the construction of the family by means of documents, architecture and midwife practices. At the same time, the article illustrates how midwife practices reproduce hierarchies of a superior white, majority ethnic, middle class norm which equals respectability, opposed to inferior non-white, minority ethnic, working class deviations.